2016
DOI: 10.1542/peds.2016-0627
|View full text |Cite
|
Sign up to set email alerts
|

Observed Effectiveness of Palivizumab for 29–36-Week Gestation Infants

Abstract: BACKGROUND: Respiratory syncytial virus (RSV) is a common reason for hospitalization of infants. In clinical trials, palivizumab reduced RSV hospitalization rates for premature infants. The 2014 American Academy of Pediatrics clinical practice guideline advised against use of palivizumab for otherwise healthy infants ≥29 weeks' gestation. The aim of this study was to determine the effect of palivizumab administration on hospitalization rates for RSV and bronchiolitis without RSV diagnosis among infants 29 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 13 publications
3
27
1
Order By: Relevance
“…However, the use of palivizumab is currently restricted to high-risk infants, as the American Academy of Pediatrics only recommends immunoprophylaxis with palivizumab during the first year of life for infants born at <29 week’s gestation with coexisting morbidities including BPD or hemodynamically unstable cardiovascular disease [85]. Such restricted use of palivizumab has been largely related to the high cost of this treatment (estimated cost for a single course approximately $US 4458 per child), as well as the uncertainty about cost-effectiveness, with recent studies reporting limited or no effect of palivizumab among otherwise healthy preterm infants born at or after 29 weeks’ gestation [8688]. To date, there is no effective acute treatment for RSV, even in high risk groups such as preterm infants.…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…However, the use of palivizumab is currently restricted to high-risk infants, as the American Academy of Pediatrics only recommends immunoprophylaxis with palivizumab during the first year of life for infants born at <29 week’s gestation with coexisting morbidities including BPD or hemodynamically unstable cardiovascular disease [85]. Such restricted use of palivizumab has been largely related to the high cost of this treatment (estimated cost for a single course approximately $US 4458 per child), as well as the uncertainty about cost-effectiveness, with recent studies reporting limited or no effect of palivizumab among otherwise healthy preterm infants born at or after 29 weeks’ gestation [8688]. To date, there is no effective acute treatment for RSV, even in high risk groups such as preterm infants.…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…The guidance remains controversial with literature in support of and against the new restrictions [4][5][6][7][8]. Farber, et al studied infants born over a three-year period between 29-36 weeks gestation without chronic illness in Texas who were enrolled in managed Medicaid.…”
Section: Original Articlementioning
confidence: 99%
“…Among those born between 29-32 weeks gestation, palivizumab prophylaxis receipt was associated with reduced hospitalization for RSV disease, but increased hospitalization for non-RSV bronchiolitis. They concluded that the more restrictive guidance of 2014 overall had little impact on this population [4]. Likewise, a study of hospital utilization of palivizumab found the restrictive guidance did not have an effect on nosocomial RSV and resulted in significant cost savings [6].…”
Section: Original Articlementioning
confidence: 99%
“…The investigators evaluated the effect of palivizumab administration on hospitalization for bronchiolitis with or without an RSV diagnosis among healthy preterm infants born at 29 to 36 weeks of gestation during their first RSV season occurring in 2012, 2013, or 2014. 4 These infants did not have conditions known to increase hospitalization rates for RSV, specifically, chronic lung disease of prematurity or congenital heart disease. Although the recommendations to limit use of palivizumab in healthy preterm infants were released in July 2014, the Texas Medicaid program did not fully adopt them until 2015.…”
mentioning
confidence: 98%
“…In this issue of Pediatrics, Farber et al 4 provide data from nine Medicaid managed care health programs in Texas supporting the 2014 recommendation. The investigators evaluated the effect of palivizumab administration on hospitalization for bronchiolitis with or without an RSV diagnosis among healthy preterm infants born at 29 to 36 weeks of gestation during their first RSV season occurring in 2012, 2013, or 2014.…”
mentioning
confidence: 99%